Estimating pension wealth of ELSA respondents - James Banks; Carl Emmerson; Gemma Tetlow (Institute for Fiscal Studies (IFS), 2005)
This paper explains the methodology used for calculating pension wealth for all individuals in the first wave of the English Longitudinal Study of Ageing (ELSA). We focus on the pension wealth of individuals aged between 50 and the state pension age. Both state and private pension wealth has been calculated and each has been calculated both on the basis of immediate retirement in 2002 and on the basis of retirement at the state pension age. Sensitivity analysis of our assumptions is also presented, which shows that the distribution of pension wealth is sensitive to our assumptions about the discount rate and contracting out histories but insensitive to assumptions about future earnings growth, future annuity rates and future asset returns.
Keywords: 330; Alterssicherung; Vermögensverteilung; Großbritannien